2013
DOI: 10.1249/mss.0b013e318285402b
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-Measured Physical Activity and Inflammation after Gestational Diabetes

Abstract: These analyses suggest that in the years after delivery, longer time spent in MVPA practice is associated with a lower cardiometabolic risk only in women with prior GDM who do not have abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Leipold et al (2006) reported that the 5G allele of the PAI-1 gene is associated with normal glucose tolerance in pregnant women independent of maternal age or BMI and it is also related to low fasting glucose values in the oral glucose tolerance test [ 108 ]. Physical activities can lower cardiometabolic risk in women with previous GDM and PAI-1 levels, as well as the level of C-reactive protein, leptin and triglycerides [ 109 ].…”
Section: Role Of Pai-1 In the Female Reproduction Systemmentioning
confidence: 99%
“…Leipold et al (2006) reported that the 5G allele of the PAI-1 gene is associated with normal glucose tolerance in pregnant women independent of maternal age or BMI and it is also related to low fasting glucose values in the oral glucose tolerance test [ 108 ]. Physical activities can lower cardiometabolic risk in women with previous GDM and PAI-1 levels, as well as the level of C-reactive protein, leptin and triglycerides [ 109 ].…”
Section: Role Of Pai-1 In the Female Reproduction Systemmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to investigate the association of the number of breaks taken during SB, measured objectively by a device, and serum lipid profiles in a healthy middle-aged female population. Previous studies have focused on PA and SB in child [ 26 , 27 ], youth [ 28 ] or adult populations with certain physiological states or illnesses [ 29 31 ] or adults with different types of professions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In young women who had GDM about seven years prior to enrolment, soluble TNF α R2 and IL-6 levels were higher than those in young women without a history of GDM [ 25 ]. In another cross-sectional study of predictors of inflammatory markers in young women ~three years after pregnancy complicated by GDM, higher waist circumference was significantly associated with higher CRP, leptin, and resistin and negatively with adiponectin [ 26 ]. Although the majority of women (~70%) did not meet recommended weekly levels of physical activity, participation in physical activity lowered cardiometabolic risk in women with prior GDM.…”
Section: Discussionmentioning
confidence: 99%